2020
DOI: 10.18332/tpc/128448
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of cigarette-butt pollution on human, animal, vegetal and environmental health: A systematic review

Abstract: is an open access, peer-reviewed online journal that encompasses all aspects of tobacco use, prevention and cessation that can promote a tobacco free society. The aim of the journal is to foster, promote and disseminate research involving tobacco use, prevention, policy implementation at a regional, national or international level, disease development-progression related to tobacco use, tobacco use impact from the cellular to the international level and finally the treatment of tobacco attributable disease thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Ultimately, these products would affect the human passing through the food chain (Mustafic et al, 2020).…”
Section: Why Is Tobacco Products' Waste An Issue Of Concern?mentioning
confidence: 99%
See 2 more Smart Citations
“…Ultimately, these products would affect the human passing through the food chain (Mustafic et al, 2020).…”
Section: Why Is Tobacco Products' Waste An Issue Of Concern?mentioning
confidence: 99%
“…After a prolonged period, this waste becomes part of the leachate and contaminates the groundwater resources as well (Singh & Bhagwat, 2022). Studies have shown that these chemicals have toxic impacts onto the aquatic and terrestrial organisms (Micevska et al., 2006; Moerman & Potts, 2011; Mustafic et al, 2020; Novotny et al, 2011; Upadhyay et al., 2022). As per the toxicity assessment report, cigarette butts soaked in fresh/salt water for 96 h have enough lethal potential to kill the fish (Slaughter et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation